1984
DOI: 10.1039/c39840000624
|View full text |Cite
|
Sign up to set email alerts
|

Photo-activation of methane at 12 K by (η5-cyclopentadienyl)- and (η5-pentamethylcyclopentadienyl)-dicarbonyl-rhodium and -iridium complexes

Abstract: evidence, including *H labelling, is presented to show that photolysis of [(q5-C5R5)M(C0),] complexes (M = Rh, R = Me; M = Ir, R = H, Me) in CH4 matrices at 12 K leads primarily to [(q5-C,R5)M(CO)(H)(Me)] species whereas in Ar and N2 matrices only small yields of {(q5-C5R5)M(CO)] species are observed. One of the most important goals in the petrochemicals [(q5-C5R5)M(CO)2] [(r5-CsMes>Ir(Co)(H)(Me)l (4) industry is to find catalysts which will activate saturated hydrocarbons, particularly CH4, so as to enable th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 2 publications
1
44
0
Order By: Relevance
“…Rest provided the first direct evidence for the intermediacy of Cp * M(CO), where M ‚ Rh or Ir, and CpIr (CO) in oxidative addition of C-H bonds with the observation of the C-H activation of methane under matrix conditions [55]. The subsequent observation that Cp * Ir-(CO)H 2 also activated methane in matrices pointed to a common electron-deficient intermediate for these processes, Scheme 8 [56].…”
Section: Oxidative Addition Of C-h Bonds Preceded By Co-lossmentioning
confidence: 98%
“…Rest provided the first direct evidence for the intermediacy of Cp * M(CO), where M ‚ Rh or Ir, and CpIr (CO) in oxidative addition of C-H bonds with the observation of the C-H activation of methane under matrix conditions [55]. The subsequent observation that Cp * Ir-(CO)H 2 also activated methane in matrices pointed to a common electron-deficient intermediate for these processes, Scheme 8 [56].…”
Section: Oxidative Addition Of C-h Bonds Preceded By Co-lossmentioning
confidence: 98%
“…This work is based on the fact that light hydrocarbon feeds typically contain alkenes. Such a mixture could be subjected to a tandem catalytic system comprising an alkene dimerization catalyst and an alkane transfer-dehydrogenation catalyst (12). The dimerization catalyst would effect coupling of two C n alkene fragments to give C 2n alkene, while the transfer-dehydrogenation catalyst could effect the dehydrogenation of C n alkane to regenerate C n alkene and transfer hydrogenation of C 2n alkene to give C 2n alkane.…”
Section: Alkane-alkene Couplingmentioning
confidence: 99%
“…Thus, the first reported examples of alkane dehydrogenation by well-defined soluble transition metal complexes were met with great interest [1][2][3][4][5][6]. Soon thereafter reports of remarkable selectivity in the stoichiometric oxidative addition of C-H bonds appeared, serving to highlight the potential offered by molecular dehydrogenation catalysts [7][8][9][10][11][12][13][14][15] (for some reviews of alkane C-H bond activation by organometallic complexes, see [16][17][18][19][20][21]). …”
Section: Introduction To Alkane Dehydrogenationmentioning
confidence: 99%
“…At the risk of over-simplification, it would probably be fair to say that the "difficulty" associated with C-H activation is typically more related to thermodynamics than to kinetics; in those cases where the thermodynamics are favorable, the kinetics are often quite facile. The classic illustration of this was offered by Graham and Rest who found that methane addition to photogenerated CpM(CO) occurred at temperatures as low as 12 K(\) (67).…”
Section: Figure 2 Double-labeling Experiments Demonstrating Intramolementioning
confidence: 99%